Hydrodynamic impact and power production of tidal turbines in a storm surge barrier - Thomas O'Mahoney; Anton de Fockert; Arnout C. Bijlsma; Pieter de Haas (International Marine Energy Journal, 2020)
To estimate the impact on energy production and environment of tidal turbines placed in the Eastern Scheldt Storm Surge Barrier a Computational Fluid Dynamics (CFD) study has been carried out on the additional head differences induced by the turbines. The CFD model focusses on a single gate opening of the Storm Surge Barrier and includes half of the adjoining gates on either side. In this 40 m wide Gate a 1.2 MW array existing of five Tocardo T2 tidal turbines has been installed as part of a demonstration project in 2015. Transient computations of the barrier with and without the turbine array were carried out for a range of quasi stationary tidal phases. The turbines are resolved in detail as rotating equipment: real-time rotation of the turbine blades (involving the displacement of the mesh nodes in an unsteady setting) is implemented, and torque and thrust for the prescribed speed of rotation is provided as output. The results for velocity, power and thrust are compared with field experiments to validate the model. Based on these computations an estimate of the effect of turbines on the discharge capacity of the storm surge barrier is given. This information will be used to parameterize the tidal turbines in the far-field hydrodynamic model of Eastern Scheldt estuary for the ultimate assessment of the effect of tidal turbines on energy production and on the environment.